30+ year evolution of Cu in the surface sediment of Lake Poyang, China. (February 2017) - Wang, Hua; Zhao, Yijun; Liang, Dongfang; Deng, Yanqing; Pang, Yong
Abstract: Poyang Lake, the largest freshwater lake in China, is increasingly experiencing Cu crises. Combining field data, laboratory experiments, and long-term simulations, we retrieved 30 + year evolution of Cu in surface sediments (SCu). SCu evolution between 1983 and 2015 may be separated into two distinguishable periods. During the first period (1983–2003), SCu underwent a continuous increase at a mean rate of 1.80 mg/kg/yr; however, since 2003 it displayed a stepwise reduction tendency. The average SCu concentration of the entire lake in 2015 fell to 54.26 mg/kg, which is approximately 30.01% lower than that in 2003. The operation of Three Gorges Dam (TGD) markedly altered the river-lake relationship, pulled more deposited Cu along with sediment out toward the Yangtze River, and made the regions of high SCu emanate from the southeastern lake extend northwestward between 2003 and 2015. SCu in the reserves showed significant inter-annual variations, with the exception of the Jiangxi Whitebait Spawning Reserve (JWSR), where SCu generally has not been significantly impacted and has displayed no departure from the 30 + year mean of 30.57 mg/kg. The National Germplasm Reserve (NGR) and Nanjishan National Nature Reserve (NNNR) were detected with the highest SCu, with the peak concentrations, respectively, of 123.15 mg/kg and 103.1 mg/kg. Graphical abstract: Highlights: Cu entered the surface sediment at varied rates in 1983–2015. The Three Gorges Dam played a pronounced role in Cu evolution. Cu in surface sediment exhibited departure among different reserves.